Ekologi yang Tersubordinasi dan Transformasi Penghidupan di Bangka Belitung Pascatambang: Dinamika Komunitas dalam Lanskap Pasca-Ekstraktif - Herdiyanti Herdiyanti; Bagong Suyanto; Siti Mas'udah (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
The long-standing tin mining industry in the Bangka Belitung Islands has left a legacy of complex ecological crises, including thousands of abandoned mining pits (kolong), land degradation, and the dislocation of local livelihoods. This study examines how local communities reconstruct their livelihood strategies within a post-extractive landscape characterized by ecological subordination, institutional fragmentation, and asymmetrical power relations. Employing a descriptive qualitative approach through content and critical discourse analysis of policy documents, institutional reports, scholarly publications, and online media coverage, the research traces how national development narratives, policy frameworks, and media representations contribute to the socio-ecological marginalization of post-mining areas in Bangka Belitung. The findings reveal that although community initiatives, such as pit reclamation, participatory agro-tourism, and freshwater aquaculture, are emerging, these efforts are often constrained by unclear land access, weak institutional support, and structural exclusion in land governance. Livelihood transformation in post-mining contexts is not linear but unfolds through politicized processes marked by spatial conflict, community agency, and contested resource control. The study underscores the need for recovery policies that are not merely technocratic, but socially and ecologically transformative, positioning local communities as principal actors. The practical implications point to reforming post-mining governance in a contextualized, participatory, and locally grounded manner to achieve long-term sustainability and ecological justice in extractive-affected regions.